Analysis of Passenger Satisfaction as a Mediator of Repurchase Intention on Flights with International Routes - Christiarini, Renny; Putra, Chanda Vedalla; Purwianti, Lily (Almana : Jurnal Manajemen dan Bisnis, 2024)
During the rise of Covid-19 pandemic, airline industry has been impacted negatively. In Indonesia, international passengersâ€™ number has been drastically reduced as the impact of the social limitations by the government and border closure between countries. But as the time goes on, numbers of vaccination found to be effective to eliminate the pandemic. With the reduced spread of the virus, number of international flights in Indonesia slowly rise to the numbers pre-pandemic. â€œRevenge Travelâ€ phenomenon has been accredited as the main source of the rise of international flights number, with passengers took their â€œdelayedâ€ holiday during the pandemic afterwards. Those rise in passenger numbers has become a challenge for airlines and airports, as the services has not been returning to the situation before the pandemic. Those challenges really impacted airlines service quality and passengersâ€™ satisfaction with their repurchase intention of buying another plane ticket with the same airline. This situation is studied in this study with the method of collecting primary data between January to May of 2024 and analysing it via PLS-SEM (Partial Least Squares-Structural Equation Model) method with the Smart-PLS application.